EFEKTIVITAS TEKNIK ROLE PLAYING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI KELAS VII SMP NEGERI 4 IDANOGAWO - Iman Kristiani Harefa; Hosianna Rodearni Damanik; Famahato Lase; Justin Foera-era Lase (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The quality of education is strongly influenced by learning processes that encourage active student engagement. Teacher-centered instruction at SMP Negeri 4 Idanogawo has contributed to the low learning motivation of seventh-grade students. This study aims to analyze the effectiveness of the role-playing technique in enhancing students’ learning motivation. The research employed a quantitative approach with a quasi-experimental design (pretest–posttest control group design). The sample consisted of 32 students divided into an experimental class and a control class. Data were collected using a learning motivation questionnaire that had met validity and reliability requirements and were analyzed using the N-gain test to measure the level of improvement in motivation. The findings revealed that the experimental class achieved an average N-gain score of 0.68, categorized as moderate to high (effective), while the control class obtained an N-gain score of 0.29, categorized as low (ineffective). This difference indicates that the implementation of the role-playing technique resulted in a more significant increase in learning motivation compared to conventional instruction. Therefore, the role-playing technique is recommended as an alternative instructional strategy to enhance students’ learning motivation in junior high schools. ABSTRAK Mutu pendidikan sangat dipengaruhi oleh proses pembelajaran yang mampu mendorong keterlibatan aktif siswa. Pembelajaran yang masih berpusat pada guru di SMP Negeri 4 Idanogawo berdampak pada rendahnya motivasi belajar siswa kelas VII. Penelitian ini bertujuan untuk menganalisis efektivitas teknik role playing dalam memperkuat motivasi belajar siswa. Penelitian menggunakan pendekatan kuantitatif dengan desain eksperimen semu (pretest–posttest control group design). Sampel penelitian berjumlah 32 siswa yang dibagi ke dalam kelas eksperimen dan kelas kontrol. Data dikumpulkan melalui angket motivasi belajar yang telah memenuhi uji validitas dan reliabilitas, kemudian dianalisis menggunakan uji N-gain untuk mengukur tingkat peningkatan motivasi. Hasil penelitian menunjukkan bahwa nilai rata-rata N-gain kelas eksperimen sebesar 0,68 yang berada pada kategori sedang–tinggi (efektif), sedangkan kelas kontrol memperoleh nilai N-gain sebesar 0,29 yang berada pada kategori rendah (tidak efektif). Perbedaan tersebut menunjukkan bahwa penerapan teknik role playing memberikan peningkatan motivasi belajar yang lebih signifikan dibandingkan pembelajaran konvensional. Dengan demikian, teknik role playing dapat direkomendasikan sebagai strategi pembelajaran alternatif untuk mendukung peningkatan motivasi belajar siswa di sekolah menengah pertama.